2012
DOI: 10.1177/0961203312442259
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of maintenance therapy with tacrolimus versus azathioprine for active lupus nephritis: a multicenter randomized clinical trial

Abstract: Aim: The optimal maintenance therapy for active diffuse lupus nephritis remains to be established. In this study, we explored the efficacy and safety of tacrolimus for maintaining remission of active lupus nephritis compared to that of azathioprine. Methods: Seventy patients with biopsy-proven lupus nephritis who achieved remission were enrolled in nine nephrology centers in China from 2006 to 2008. Patients were randomized either to tacrolimus plus prednisone ( n = 34) or azathioprine plus prednisone ( n = 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 20 publications
1
50
0
1
Order By: Relevance
“…Finally, it is worth noting that renal relapses were recorded during therapy with MF in about 20% of the patients in most studies, as well as in ours. Therefore, other therapeutic schedules (based mainly on calcineurin inhibitors) have been tried, with promising results [14,17,27]. In fact, 4 patients in our study took other immunosuppressive drugs (3 calcineurin inhibitors and 1 rituximab) while taking MF; however, their low number prevented us from drawing solid conclusions about efficacy.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Finally, it is worth noting that renal relapses were recorded during therapy with MF in about 20% of the patients in most studies, as well as in ours. Therefore, other therapeutic schedules (based mainly on calcineurin inhibitors) have been tried, with promising results [14,17,27]. In fact, 4 patients in our study took other immunosuppressive drugs (3 calcineurin inhibitors and 1 rituximab) while taking MF; however, their low number prevented us from drawing solid conclusions about efficacy.…”
Section: Discussionmentioning
confidence: 64%
“…During the last decade, the results of at least 9 trials have been reported [8,9,11,12,13,14,15,16,17], and several retrospective studies [18,19,20] have focused on the best drug schedule in the maintenance phase of treatment of LN. The results allow us to conclude that short-term induction with intravenous CYC followed by maintenance therapy with MF or AZA was more efficacious than other treatment schedules [11,12,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available clinical trials propound sequential therapy as an effective and safe alternative for treating severe LN in patients of white, Asian, African, or Hispanic ancestry (18)(19)(20)(21)(22)(23)(24)(25)(26). We have seen a comforting decline in CKD (7% or less) and mortality (10% or less) with the use of sequential therapies in the past two decades.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Subsequently, several reports have noted the efficacy of TAC for nephritis. [18][19] [20] Maintenance therapy of SLE has been reported only in studies of patients with lupus nephritis or without lupus nephritis, [21][22] [23] and in a small group study and a short-duration study. [24][25] Thus, there have been no previous assessments of long-term TAC therapy in a larger group of SLE patients with/without nephropathy, as performed in this study.…”
Section: Discussionmentioning
confidence: 99%